Glyphosate and aminomethylphosphonic acid in human hair quantified by an LC‐MS/MS method. (16th May 2022) - Alvarez, Jean‐Claude; Etting, Isabelle; Larabi, Islam Amine
Abstract: An LC‐MS/MS method for hair testing of glyphosate and aminomethylphosphonic acid (AMPA), its main biodegradation product, has been developed. After decontamination, 50 mg of hair was ground and sonicated in water for 2 h. The method was fully validated in the 5–500 pg/mg range for glyphosate and 10–500 pg/mg for AMPA, and the limits of detection were 2 and 5 pg/mg, respectively. Matrix effect for glyphosate and AMPA was compensated by an isotope‐labeled internal standard. Hair samples from four farmers who regularly used glyphosate and one farmer who used glyphosate but not his wife and 14 hair samples from nonoccupationally exposed subjects were tested. Glyphosate was found in head hair of three farmers, with concentration in the range 14–188 pg/mg. The fourth was found negative but with hair colored in red. Glyphosate was detected in 10 of 14 hair samples from nonoccupationally exposed subjects at concentrations of 11.5 pg/mg or lower and only in one segment (0–3 cm) of the farmer's spouse (6 pg/mg). AMPA was detected in five subjects, above the limit of quantification only in two of three occupationally exposed subjects with positive glyphosate. Further studies should be conducted to validate this potential new biomarker that could be useful for assessing long‐term exposure to glyphosate.